Simulation Method In Programmable Logic - Sumilat, J M; Seke, F R; Mantiri, J (Journal of Educational Method and Technology, 2018)
Programmable logic controller (PLC) is a microprocessor used to automate industry processes such as controlling a factory's engine. As a candidate in electrical engineering degree must be able to assemble and arrange PLC control program so that later can compete in industrial world. Therefore PLC is one of the compulsory courses that must be pursued. But in learning PLC encountered obstacles that students feel less interested in learning that they need to understand the language of logic, and require them to assemble the series of automation with inadequate equipment, so we think Simulation learning method is a learning method can improve the students' understanding of the situation or problem better. The purpose of this research is to know the effect of simulation learning method on students with high and low creativity level in PLC learning. The method used in this research is an experimental method. Result of this study is simulation learning method can improve learning result of PLC, but not maximal. PLC learning requires real work practices so as to provide accurate knowledge to every student.Based on these conclusions, the suggestion in PLC learning can use a learning method that uses work practices as a learning tool of PLC